New records of Cyathea atrovirens (Langsd. & Fisch.) Domin (Cyatheaceae) from Argentina - Ernesto Krauczuk; Gonzalo Marquez; Héctor Keller (Check List, 2015)
Cyathea atrovirens (Cyatheaceae) is the southernmost tree-fern of Argentina and its presence in the Corrientes province was in doubt after the height of the Yacyretá dam was raised. However, new records confirm the presence of the species in the province and increase the range distribution southward. Comments on the distribution and ecology of the species are now reported.